Molecular subtypes of a bladder cancer: evolution of classifications and clinical significance - O. N. Sulaieva; A. A. Seleznov; D. A. Shapochka; A. E. Stakhovskiy; R. N. Ponomarchuk; P. N. Botsun (Клінічна хірургія)
Molecular subtypes of a bladder cancer: evolution of classifications and clinical significance